Metacognição na formação e atuação do médico: o que as pesquisas têm a nos dizer? - Estacia, Carolina Tagliari (2024)
The study analyzes the occurrence of metacognition in scientific articles in the health area, particularly those linked to the training and performance of doctors. The importance of metacognition as part of the doctor's training and professional process is linked to the need to seek balance between the knowledge presented in the literature and present in academic training, the clinical reasoning of the case under analysis, the exercise of professional practice and the character and professionalism (Botti; Rego, 2010). This balance refers to a reflective process that can be favored if accompanied by thinking about one's own thinking, that is, metacognitive thinking. Based on these considerations, the study questions how this way of thinking has been explored in national and foreign research that deals with teaching-learning processes linked to the training and performance of doctors. The main question consists of the following question: what characteristics are identified in the scientific production that articulates metacognition with the doctor's learning processes? The objective is to investigate how metacognition is articulated in national and foreign research published in articles that deal with learning processes linked to the training and performance of doctors. To achieve the proposed objective and answer the research question, a state of knowledge bibliographical research was carried out, selecting five databases as locus of investigation: Education Resources Information Center (ERIC), SciELO, Web of Science (WoS) , Scopus and PubMed. On these bases, and from a combination of descriptors involving "metacognition" and "Medicine", 1,013 studies were identified, of which 17 were selected to constitute the research corpus. These articles, after being read in full, were reported in the text and analyzed based on two categories: (i) Overview of studies and (ii) Metacognition and physician learning. Each category is divided into subcategories that include the results found. Of the analyzes carried out, with regard to the first category (Overview of studies), the largest number of publications is found in 2021; the United States and Brazil are the countries with the largest number of studies; the Brazilian Journal of Medical Education and Instructional Science are the journals with the largest number of publications; and the target audience for the research is concentrated on medical students. The second category (Metacognition and physician learning) was structured into two subcategories, one associated with the assessment of metacognitive thinking and the other, with the presence of metacognition in the studies analyzed. In the first subcategory, the results indicate that questionnaires are the most used instruments in research, with emphasis on the Metacognitive Awareness Inventory (MAI). In the second subcategory, two aspects were identified: metacognition as a learning strategy, present in 12 of the 17 studies, and metacognition as medical decision-making, being the focus of four of the 17 studies. As a final result, the study points out that, given the universe investigated and in terms of the link between metacognition and doctor's learning, the articles are limited in number, but with the possibility of expansion from the year 2021; the research center specialized in the topic identified was in Brazil and there is no magazine dedicated to the topic that covers a greater number of publications; there is a predominance of research that seeks to identify characteristics of the metacognitive thinking of medical students; and there is an understanding that metacognitive thinking acts as a learning strategy.